2017
DOI: 10.7554/elife.28844
|View full text |Cite
|
Sign up to set email alerts
|

An Aedes aegypti-associated fungus increases susceptibility to dengue virus by modulating gut trypsin activity

Abstract: Transmission of dengue virus (DENV) requires successful completion of the infection cycle in the Aedes aegypti vector, which is initiated in the midgut tissue after ingestion of an infectious blood meal. While certain Ae. aegypti midgut-associated bacteria influence virus infection, little is known about the midgut-associated fungi (mycobiota), and how its members might influence susceptibility to DENV infection. We show that a Talaromyces (Tsp_PR) fungus, isolated from field-caught Ae. aegypti, render the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 37 publications
0
69
0
Order By: Relevance
“…A poorly understood aspect of the ecology of insects involves their interactions with yeasts and how these affect their immunity [52], distribution [53], and vector competence [54]. Yeasts in plant nectar secrete byproducts of fermentation that function as signals for insects to identify food sources.…”
Section: Beyond Plant Odormentioning
confidence: 99%
“…A poorly understood aspect of the ecology of insects involves their interactions with yeasts and how these affect their immunity [52], distribution [53], and vector competence [54]. Yeasts in plant nectar secrete byproducts of fermentation that function as signals for insects to identify food sources.…”
Section: Beyond Plant Odormentioning
confidence: 99%
“…The aforementioned studies indicate that S. marcescens is a critical bacterium for regulating the mosquito susceptibility to arboviral infection. Indeed, S. marcescens is an indigenous gut commensal bacterium identified in field-caught mosquitoes frequently (Anglero-Rodriguez et al, 2017;Ramirez et al, 2012). We next assessed whether S. marcescens-mediated regulation of the gut microbial ecology might influence the vector competence of low-passage field-derived mosquitoes.…”
Section: S Marcescens Enhances the Vector Competence Of Field Mosquimentioning
confidence: 99%
“…Gut commensal bacteria limit viral infections by priming the host immune surveillance and secreting microbial metabolites (Hegde et al, 2015;Jupatanakul et al, 2014). Nonetheless, a recent study demonstrated that a Talaromyces fungus in the Aedes aegypti gut increased the mosquitoes' permissiveness to dengue virus (DENV) infection by modulating the digestive enzymes and trypsin activity of the mosquito gut (Anglero- Rodriguez et al, 2017), suggesting complicated roles for the gut commensal microbiome in arboviral infection and transmission. In this study, we identify a gut bacterium, Serratia marcescens, that has a role in promoting arboviral infection of mosquitoes.…”
Section: Introductionmentioning
confidence: 99%
“…This very promising tactic, to enhance proteolysis in the guts of insect vectors, may be broadly applied to control transmission of vector-borne animal infecting viruses. In this respect, Anglero-Rodriguez, Dimopoulos and colleagues showed that gut infection by a Talaromyces fungi in Aedes aegypti caused a downregulation of proteolytic enzymes and enhanced susceptibility to dengue virus [53]. In aphids, experimenting with intercropping alternative host plants may be one way to interfere with the ability of migrating aphids to transmit virus into a crop.…”
Section: Methods 2: Block Virus Acquisition and Inoculation By Manipulmentioning
confidence: 99%